Perbandingan Hasil Belajar antara Siswa Madrasah Diniyah dengan Siswa Non-Madrasah Diniyah pada Mata Pelajaran PAI di Madrasah Tsanawiyah - Mufarihah, Ayu Fatihatul; Anwar, M. Ansor (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2019)
This research is motivated by the learning outcomes of the Madrasah Diniyah (Islamic School) and Non-Madrasah Diniyah students in the Sayyid Abdurrahman Islamic Junior High School (Madrasah Tsanawiyah). The purposes of this study are to find out whether there are differences between students who take part in the Madrasah Diniyah and students who did not take part in the Madrasah Diniyah. The design of this study is included in the type of quantitative research. The type of quantitative research is the method of collecting observation and documentation data. The analysis technique uses the free t test statistical formula. Data analysis using SPSS. The research samples are 54 students. The percentage of students of the Madrasah Diniyah is considered â€œgoodâ€ because 89:14% included the 76%-100% category. And the percentage of Non-Madrasah Diniyah students is â€œquite goodâ€ because 75.96% belongs to the 51%-75% category. Thus it can be concluded that there is a comparison between the Madrasah Diniyah students and the Non-Madrasah Diniyah students in the Sayyid Abdurrahman Islamic Junior High School. With the hypothesis that Ha is accepted and H0 is rejected.